SOME OBSERVATIONS ON THE LIBERATION AND VIABILITY OF OOSPORES IN SARGASSUM WIGHTII (GREVILLE) J. AGARDH - Rao, M Umamaheswara; Kaliaperumal, N (Indian Journal of Fisheries, 2011)
Some observations made on the output and viability of oospores in Sargassum wightii are presented. iMiaximum output of healthy spores was observed for seven days in the laboratory experiments, without any periodicity in the Eberation of oospores. Spore-shedding season extends for three months, from November to January, with the highest value in December. In viability experiments 47.6% of the sporelings have been found in healthy condition at the end of 60 days.